Identification of Student Misconceptions on Dynamic Fluid Material using a Five-tier Diagnostic Test - Hazmi, Hanifah Rahmania; Jauhariyah, Mukhayyarotin Niswati Rodliyatul (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Misconception is one of the problems that often occurs in physics learning, especially in dynamic fluid materials. Misconceptions can affect physics learning outcomes if allowed to occur continuously. This study aims to identify students' misconceptions about dynamic fluid material using a five-tier diagnostic test. Five-tier diagnostic test is the newest form of diagnostic test that is able to detect deeper misconceptions experienced by students. By using the five-level diagnostic test, you will be able to see dynamic fluid material that still has misconceptions and requires more emphasis. Apart from that, teachers can design remediation learning better. This study employed a one-shot research method with a sample of 68 students from class XI of a high school who had received dynamic fluid material. The result of this study is that students experience misconceptions on dynamic fluid material, with an average percentage of 40.7% in the moderate category. Students' misconceptions on dynamic fluid material occur in the sub-matter of the principle of continuity and Bernoulli's Law. The misconceptions experienced by students in the continuity principle sub-matter regarding the relationship between cross-sectional area (A) and fluid velocity (v) by 37,5%, the relationship between cross-sectional area (A) and fluid debit (Q) by 46,9%, and the relationship between cross-sectional area (A) and volume (V) by 50%, with a moderate category. Meanwhile, in the Bernoulli's Law sub-matter, students experienced misconceptions regarding the relationship between the depth of the leak hole (h) and the distance of the fluid jet (x) by 40,6%, and the relationship between velocity (v) and fluid pressure (P) by 43,8% with moderate categories. Given the misconceptions students still experience with dynamic fluid materials, it is necessary to implement remediation strategies, such as tests, special learning methods, or assignments.